Imaging in gynecological disease (10): clinical and ultrasound characteristics of decidualized endometriomas surgically removed during pregnancy. (September 2014) - Mascilini, F.; Moruzzi, C.; Giansiracusa, C.; Guastafierro, F.; Savelli, L.; De Meis, L.; Epstein, E.; Timor‐Tritsch, I. E.; Mailath‐Pokorny, M.; Ercoli, A.; Exacoustos, C.; Benacerraf, B. R.; et al.
ABSTRACT Objectives To describe the clinical history and ultrasound findings in women with decidualized endometriomas surgically removed during pregnancy. Methods In this retrospective study, women with a histological diagnosis of decidualized endometrioma during pregnancy who had undergone preoperative ultrasound examination were identified from the databases of seven ultrasound centers. The ultrasound appearance of the tumors was described on the basis of ultrasound images, ultrasound reports and research protocols (when applicable) by one author from each center using the terms and definitions of the International Ovarian Tumor Analysis (IOTA) group. In addition, two authors reviewed together available digital ultrasound images and used pattern recognition to describe the typical ultrasound appearance of decidualized endometriomas. Results Eighteen eligible women were identified. Median age was 34 (range, 20–43) years. Median gestational age at surgical removal of the decidualized endometrioma was 18 (range, 11–41) weeks. Seventeen women (94%) were asymptomatic and one presented with pelvic pain. In three of the 18 women an ultrasound diagnosis of endometrioma had been made before pregnancy. The original ultrasound examiner was uncertain whether the mass was benign or malignant in 10 (56%) women and suggested a diagnosis of benignity in nine (50%) women, borderline in eight women (44%), and invasive malignancy in one (6%) woman. Seventeen decidualized endometriomas contained a papillary projection, and in 16 of these at least one of the papillary projections was vascularized at power or color Doppler examination. The number of cyst locules varied between one (n = 11) and four. No woman had ascites. When using pattern recognition, most decidualized endometriomas (14/17, 82%) were described as manifesting vascularized rounded papillary projections with a smooth contour in an ovarian cyst with one or a few cyst locules and ground‐glass or low‐level echogenicity of the cyst fluid. Conclusions Rounded vascularized papillary projections with smooth contours within an ovarian cyst with cyst contents of ground‐glass or low‐level echogenicity are typical of surgically removed decidualized endometriomas in pregnant women, most of whom are asymptomatic. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd